Hogtown Diary I: Edward the Caterpillar - Macdonald, Andrew (UnderCurrents: Journal of Critical Environmental Studies, 1999)
Emerge just shy of a culvert on the valley floor, dart across yellow-lined (park)way, monkey over a fence and drop down beside a moist bed of reeds, border of an abandoned rail line. All vigour and curiosity. Gingerly slippin' through eye-high cattails, crossin' cut-gravel and twin steel spines: Union Station curvatures. [...]